Հայ հոգևոր երաժշտության ծագումը, զարգացումը և ազդեցությունը մարդու տագնապայնության նվազեցման վրա - Զարուհի Հակոբյան (ՀՀ ԳԱԱ հրատ.)
В статье представляется история духовной музыки, динамика ее развития, роль в сокращении тревожности людей и позитивное влияние на психическое и физическое развитие человека. Результаты исследований представлены на основе математической статистики и критерия Уилкоксона.The article presents the history of sacred music, the dynamics of its development, its role in the anxiety reduction of people and the positive influence of sacred music on the mental and physical development. The results of research are presented based on mathematical statistics and Wilcoxon critirion.
Keywords: M Music and Books on Music; Psychology; Music